Structure and Conductivity Correlation in NASICON Based Na3Al2P3O12 Glass: Effect of Na2SO4 - Mandal, Indrajeet; Chakraborty, Saswata; Ghosh, Manasi; Dey, Krishna K.; Annapurna, K.; Allu, Amarnath R. (Frontiers in Materials, 2022)
Identifying the factors influencing the movement of sodium cations (Na+) in glasses accelerates the possible options of glass-based solid electrolyte materials for their applications as a promising electrolyte material in sodium-ion batteries. Nevertheless, due to the poor correlation between the structure and conductivity in glass materials, identifying the factors governing the conductivity still exists as a challenging task. Herein, we have investigated the DC-conductivity variations by correlating the structure and conductivity in sodium superionic conductor (NASICON) based Na3Al2P3O12 (NAP) glass (mol%: 37.5 P2O5—25.0 Al2O3—37.5 Na2O) due to the successive substitution of Na2SO4 for Al2O3. Structural variations have been identified using the Raman and magic-angle spinning nuclear magnetic resonance (MAS-NMR) (for 31P, 23Na, and 27Al nuclei) and conductivity measurements have been done using the impedance spectroscopy. From the ac-conductivity spectra, the correlations between mean square displacement (MSD) and dc-conductivity and between the Na+ concentration and dc-conductivity have also been evaluated. Raman spectra reveal that the increase in the Na2SO4 concentration increases the number of isolated SO42− sulfate groups that are charge compensated by the Na+ cations in the NAP glass. MAS-NMR spectra reveal that the increase in Na2SO4 concentration increases the concentration of non-bridging oxygens and further neither S-O-P nor S-O-Al bonds are formed. Impedance spectroscopy reveals that, at 373 K, the DC conductivity of the NAP glass increases with increasing the Na2SO4 up to 7.5 mol% and then decreases with the further increase. In the present study, we have shown that the mobility of sodium cations played a significant role in enhancing the ionic-conductivity. Further, we have shown that inter-ionic Coulombic interactions and the structural modification with the formation of SO42− units significantly influence the critical hopping length < R2 (tp)> of the sodium cations and consequently the mobility and the ionic conductivity. The present study clearly indicates that, based on the compositions, glass materials can also be treated as strong-electrolyte materials.